2009
DOI: 10.1007/s10620-009-0745-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Involvement in Thioacetamide-Induced Experimental Liver Fibrosis and Cirrhosis

Abstract: Platelet-activating factor (PAF) is a potent lipid inflammatory mediator acting on cells through its specific receptor. Plasma PAF-acetylhydrolase (PAF-AH) is the main enzyme that inactivates PAF in blood, participating in its homeostasis. The objective of this study was to investigate the involvement of PAF in the liver fibrotic process using an experimental animal model. Liver fibrosis was induced in adult male Wistar rats by administration of thioacetamide (TAA) in drinking water (300 mg/l) for three months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
2
11
0
1
Order By: Relevance
“…In accordance with previous reports (Karantonis et al, 2010;Shaker et al, 2010), the study presented here confirmed that TAA treatment resulted in a significant retardation of natural body growth, liver hypertrophy, elevated serum biomarkers of liver function, and the progressive liver fibrosis. As expected, SLE and DDB treatments exhibited powerful hepatoprotective effects, supported by the significant recovery of most indexes determined.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous reports (Karantonis et al, 2010;Shaker et al, 2010), the study presented here confirmed that TAA treatment resulted in a significant retardation of natural body growth, liver hypertrophy, elevated serum biomarkers of liver function, and the progressive liver fibrosis. As expected, SLE and DDB treatments exhibited powerful hepatoprotective effects, supported by the significant recovery of most indexes determined.…”
Section: Discussionsupporting
confidence: 93%
“…There is evidence of PAF involvement in fibrosis in different organs, like liver and lung. 39,40 In our study, the attenuated renal dysfunction observed in PAFR KO mice correlated with lower levels of fibrosis. This is in accordance with results from Doi et al, 41 using the acid folic model of renal injury.…”
Section: Discussionsupporting
confidence: 58%
“…This increase would be related with a higher deposition of collagen in the liver because PAF signaling appears to be important to trigger fibrogenesis [47,51,52]. Moreover, the use of a PAF antagonist decreases fibrosis in other tissues such as lung and subretinal tissues [53,54].…”
Section: Accepted Manuscriptmentioning
confidence: 99%